2018
DOI: 10.1108/jabes-10-2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management practices and firm outcomes: evidence from Vietnam

Abstract: Purpose-The purpose of this paper is to estimate the effects of human resource management (HRM) practices on firm outcomes at the firm level in Vietnam. Design/methodology/approach-The paper employs a fixed-effects framework for the estimation using a panel sample of manufacturing firms from small-and medium-sized enterprise surveys between 2009 and 2013. Findings-The paper finds that, on average, a firm that provides the training for new workers gains roughly 13.7, 10 and 14.9 percent higher in output value p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
4
0
5
Order By: Relevance
“…Hoang et al (2018) concluded that human capital and social capital are strongly linked to firm performance when a study using data from 319 Vietnamese information communication technology (ICT) firms. Dang et al (2018) examined the impact of human resource management on the productivity of small and medium enterprises in Vietnam. The authors argued that the more frequent a firm provides training to new employees, the greater the productivity is.…”
Section: Human Capital and Firm Performance In Vietnammentioning
confidence: 99%
“…Hoang et al (2018) concluded that human capital and social capital are strongly linked to firm performance when a study using data from 319 Vietnamese information communication technology (ICT) firms. Dang et al (2018) examined the impact of human resource management on the productivity of small and medium enterprises in Vietnam. The authors argued that the more frequent a firm provides training to new employees, the greater the productivity is.…”
Section: Human Capital and Firm Performance In Vietnammentioning
confidence: 99%
“…Para Steijvers, Lybaert y Dekker (2017) cuando las prácticas de RRHH como el reclutamiento, la evaluación y la compensación son planeadas e implementadas formalmente, contribuyen al mejoramiento del desempeño general de las PyMEs. A lo que Dang et al (2018) suman el trabajo en equipo, el pago de incentivos a los trabajadores y la capacitación. Por tal motivo la GRH ha cobrado relevancia en la sobrevivencia de estas organizaciones (Pérez-Bustamante et al, 2016) porque contribuye a su productividad, rendimiento e innovación (Dang et al, 2018).…”
Section: Marco De Referenciaunclassified
“…A lo que Dang et al (2018) suman el trabajo en equipo, el pago de incentivos a los trabajadores y la capacitación. Por tal motivo la GRH ha cobrado relevancia en la sobrevivencia de estas organizaciones (Pérez-Bustamante et al, 2016) porque contribuye a su productividad, rendimiento e innovación (Dang et al, 2018).…”
Section: Marco De Referenciaunclassified
See 2 more Smart Citations